A method for increasing the speed of digital integrating homogeneous quasi-parallel structures - Жабин, В. И.; Ковалев, Н. А. (Problems of Informatization and Control, 2008)
The possibility to accelerate the processes of integration in digital integrating machines by reducing the number of steps vichisleny through the use of redundant number systems with large grounds